The Role of Heparanase and Sulfatases in the Modification of Heparan Sulfate Proteoglycans within the Tumor Microenvironment and Opportunities for Novel Cancer Therapeutics - Hammond, Edward; Khurana, Ashwani; Shridhar, Viji; Dredge, Keith (Frontiers in Oncology, 2014)
Heparan sulfate proteoglycans (HSPGs) are an integral and dynamic part of normal tissue architecture at the cell surface and within the extracellular matrix (ECM). The modification of HSPGs in the tumour microenvironment is known to result not just in structural but also functional consequences which significantly impact cancer progression. As substrates for the key enzymes sulfatases and heparanase, the modification of HSPGs is typically characterised by the degradation of heparan sulfate (HS) chains/sulfation patterns via the endo–6-O-sulfatases (Sulf1 and Sulf2) or by heparanase, an endo-glycosidase that cleaves the HS polymers releasing smaller fragments from HSPG complexes. Numerous studies have demonstrated how these enzymes actively influence cancer cell proliferation, signalling, invasion and metastasis. The activity or expression of these enzymes have been reported to be modified in a variety of cancers. Such observations are consistent with the degradation of normal architecture and basement membranes which are typically compromised in metastatic disease. Moreover, recent studies elucidating the requirements for these proteins in tumour initiation and progression exemplify their importance in the development and progression of cancer. Thus, as the influence of the tumour microenvironment in cancer progression becomes more apparent, the focus on targeting enzymes that degrade HSPGs highlights one approach to maintain normal tissue architecture, inhibit tumour progression and block metastasis. This review discusses the role of these enzymes in the context of the tumour microenvironment and their promise as therapeutic targets for the treatment of cancer.